The business risks of using smartphones. (November 2015) - Beckett, Phil
Abstract : It seems that a lot of businesses are still unaware of the risks involved with employees using their own smartphones for business purposes. The truth is that even 'wiped' smartphones can actually retain a lot more information than their owners realise, from call and web browser history to photographs and files.